English Curriculum and Material Development - Andi Farid Baharuddin (EDULEAD: Journal of Christian Education and Leadership, 2023)
One of the most significant things that EFL students at the university level should understand is the English education curriculum program. Curriculum and syllabus are discussed in the program as the procedures of preparing, constructing, and delivering the teaching material to whom the teaching material is presented. This book goes into detail about language curriculum and creating appropriate materials for language teaching. However, in this article, I did not only examine the book's basic theme, but I also assessed its weaknesses, strengths, and challenges. In this section, I first demonstrated the principle ideas in Rochmawati's book. Second, I criticized various themes that were left out of the book.AbstrakSalah satu hal terpenting yang harus dipahami oleh siswa EFL di tingkat universitas adalah program kurikulum pendidikan bahasa Inggris. Kurikulum dan silabus dibahas dalam program sebagai tata cara, menyiapkan (topik), menyusun, dan menyajikan bahan ajar kepada siapa bahan ajar itu disajikan. Buku ini menjelaskan secara rinci tentang kurikulum bahasa dan membuat bahan yang tepat untuk pengajaran bahasa. Namun, dalam artikel ini, saya tidak hanya mengupas tema dasar buku tersebut, tetapi juga menilai kelemahan, kekuatan, dan tantangannya. Di bagian ini, saya pertama kali mendemonstrasikan ide-ide prinsip dalam buku Rochmawati. Kedua, saya mengkritik berbagai tema yang tidak dicantumkan dalam buku ini.